2017
DOI: 10.12681/jhvms.15449
|View full text |Cite
|
Sign up to set email alerts
|

Παρουσία ανθεκτικών στη μεθικιλίνη Staphylococcus aureus σε γάλα και γαλακτοκομικά προϊόντα

Abstract: Staphylococcus aureus is an opportunistic Gram positive pathogen and the causative agent of many human and animal diseases. It is also an important human foodborne pathogen. Certain strains of S. aureus can produce staphylococcal enterotoxins (SEs) in foods and cause staphylococcal food poisonings (SFP). In recent years S. aureus has been increasingly associated with antibiotic resistance. Methicillin-resistant S. aureus (MRSA) includes those strains that have acquired genes conferring resistance to methicilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…In general, VRSA in livestock may come from viscera-contaminated meat during slaughter or from the hands of employees in slaughterhouses, and colonization could pose a potential risk for zoonotic disease transmission [24, 27]. Most of these types of contamination events are of greater concern in Asia and Africa than in Europe, the USA, and Canada [28].…”
Section: Discussionmentioning
confidence: 99%
“…In general, VRSA in livestock may come from viscera-contaminated meat during slaughter or from the hands of employees in slaughterhouses, and colonization could pose a potential risk for zoonotic disease transmission [24, 27]. Most of these types of contamination events are of greater concern in Asia and Africa than in Europe, the USA, and Canada [28].…”
Section: Discussionmentioning
confidence: 99%
“…Alizadeh and Amini (10) reported that 60% of S. aureus samples isolated from dairy products in Kerman province in Iran harbored the mecA gene. Pexara et al (15), showed that the highest prevalence of methicillin-resistant S. aureus (MRSA) in milk and dairy products is found in Ethiopia (60.3%); whereas the MRSA prevalence in Asian countries is variable (for instance, while it is 28.3% in Iran, it is very low in Korea and Japan). The MRSA prevalence in dairy products has been reported to be low in European countries.…”
Section: Discussionmentioning
confidence: 99%
“…The MRSA prevalence in dairy products has been reported to be low in European countries. In addition, the strains prevalence in USA and Canada have been reported as zero to low (15). The MRSA prevalence varies in different countries in the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was reported that, E. coli O157:H7 was isolated from fecal samples of calves. 102 The pathogenic E. coli is carried in the intestinal tract and excreted in the feces, and also present on the skin which can be transferred to carcass during evisceration. The contaminate during slaughter may cause the spread of E. coli to carcass and the human can be infected after consumption.…”
Section: Study Of Pathogenic Bacteriamentioning
confidence: 99%